UMP Publisher's e-book won a silver medal at ITEX - Shalfarina, Shahriman (Penerbit UMP, 2014)
For their efforts to being able to acculturate online learning and generating income, Universiti Malaysia Pahang (UMP) Publisher was awarded a silver medal at the International Invention, Innovation and Technology Exhibition (ITEX) that was held last May.